KARAKTERISTIK FISIKOKIMIA DAN SENSORIS MINUMAN INSTAN EKSTRAK BERAS HITAM BERDASARKAN KONSENTRASI MALTODEKSTRIN DENGAN METODE FOAM-MAT DRYING - Ilham Margining Tri Utami; Nurhidajah Nurhidajah; Muhammad Yusuf (Universitas Muhammadiyah Semarang, 2023)
Black rice is one of the local varieties that has the best pigments, especially anthocyanins, compared to white rice and other rice. One of the uses of black rice as a functional food is the manufacture of ready-to-drink instant drinks that can maintain product quality and do not have added preservatives. The purpose of this study was to determine the physicochemical characteristics including anthocyanin levels, antioxidant activity, color intensity, and sensors with the addition of maltodextrin concentration..The research procedure was carried out first, black rice extraction, making black rice extract instant drink, and black rice extract instant drink formulation. The results showed that increasing the concentration of maltodextrin had a significant effect on physicochemical characteristics (anthocyanin levels, antioxidant activity, color intensity) and sensory (color and taste), but had no significant effect on sensory (aroma). The best treatment for an instant drinks with black rice extract is based on physicochemical tests, namely anthocyanin content (15.40mg/g), antioxidant activity (58.14%RSA), color intensity °Hue (41.02) Red and sensor test has a score of (3.45) close to like , contained in the addition of 30% maltodextrin concentration.